2005
DOI: 10.1108/10222529200500011
|View full text |Cite
|
Sign up to set email alerts
|

An empirical analysis of career choice factors that influence first‐year Accounting students at the University of Pretoria: A cross‐racial study

Abstract: This cross-cultural study examined the career choices of Asian, black and white students at the University of Pretoria to identify the factors motivating Accountancy students to become chartered accountants (CAs), as only 2.5% (609) of 24 308 registered CAs in South Africa in 2005 were black, and only 6% (1573) were Indian. Understanding the attitudes and the perceptions of CA first-year students (identifying key career choice factors) can help course administrators/curriculum designers (the South African Inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
52
2
9

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(75 citation statements)
references
References 13 publications
(21 reference statements)
9
52
2
9
Order By: Relevance
“…An appropriate assessment standard, combined with sufficient feedback, assists students in setting their own, realistic goals (Seymour et al, 2005;Walstrom et al, 2008). Using an example from another discipline, students identified performance in accounting at school as the most important factor in selecting accounting as their future career (Myburgh, 2005).…”
Section: Insufficient Exposure To Relevant and Representative Informamentioning
confidence: 99%
“…An appropriate assessment standard, combined with sufficient feedback, assists students in setting their own, realistic goals (Seymour et al, 2005;Walstrom et al, 2008). Using an example from another discipline, students identified performance in accounting at school as the most important factor in selecting accounting as their future career (Myburgh, 2005).…”
Section: Insufficient Exposure To Relevant and Representative Informamentioning
confidence: 99%
“…Esse resultado contradiz estudos comparativos na literatura nacional e internacional, como os de Allen (2004), Aranya et al(1978), Azevedo et al (2008, Baker (1976), Baldvinsdottir et al (2009), Bedeian et al(1986, Booth e Winzar (1993), Byrne e Willis (2005), Chan e Ho (2000), Coate et al (2003), Cohen e Hanno (1993), Diptiana e Djuwari (2007), England (1988), Francisco et al (2003), Hunt et al (2004), Michaels e Levas (2003); Myburgh (2005), Noel et al(2003), Paolillo et al (1983), Saemann e Crooker (1999), Schlee et al (2007), Sugahara e Boland (2006) Em uma situação de rivalidade, como a apresentada por estudantes de administração, economia, direito, dentre outros, por mercado de trabalho comum, é de se esperar que a percepção negativa sobre os contadores possa ser distorcida em relação à percepção pública geral.…”
Section: Análise Dos Resultadosunclassified
“…No entanto, o tema deve obedecer concomitantemente aos princípios da importância, da originalidade e da viabilidade, para que seja categorizado como pesquisa científica. Nesse sentido, Castro (1978) , 2000;ALLEN, 2004;ARANYA et al, 1978;AZEVEDO et al, 2008;BAKER, 1976;BALDVINSDOTTIR et al, 2009;BEDEIAN et al, 1986;BOOTH;WINZAR, 1993;BYRNE;WILLIS, 2005;CHAN;HO, 2000;COATE et al, 2003;COHEN;HANNO, 1993;DIPTIANA;DJUWARI, 2007;ENGLAND, 1988;FRANCISCO et al, 2003;FRIEDMAN;LYNE, 2001;HUNT et al, 2004;IMADA et al, 1980;MCPHERSON, 1999;MYBURGH, 2005;NOEL et al, 2003;PAOLILLO et al, 1983;SAEMANN;CROOKER, 1999;SCHLEE et al, 2007; SCHLOEMER; SCHLOEMER, 1997;SUGAHARA et al, 2008) ou professores (HARDIN et al, 2000;FIEGER, 2006), controllers (HOFFJAN, 2004;VAIVIO;KOKKO, 2006), clientes (HOOPER et al, 2009), ou ainda indiretamente por meio das artes, na representação dos profissionais de ...…”
Section: Objetivo E Problema De Pesquisaunclassified
“…Students may therefore choose their occupations based partly on society's stereotypical representation of that career (DeCoster, 1971, p.47). Cohen and Hanno (1993) and Felton et al, (1995) suggested that students' perceptions, and ultimately their career choices, can also be influenced by subjective norms, being the social pressure from a person related to the student, such as a parent, relative, friend, teacher, administrator or counsellor (Palillo and Estes, 1982, Gul et al, 1989and 1992, Ahmed et al, 1997and Myburgh, 2005. In addition to these subjective norms Byrne and Willis (2005) added that students' key sources of information about the profession may also include the study of accounting at secondary school and the factual media.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous empirical studies have concluded that students' perceptions of the accounting profession are greatly influenced by, inter alia, secondary school teachers (Paolillio and Estes, 1982;Gul et al, 1989;Graves et al, 1993;Cohen and Hanno, 1993;Nelson and Deines, 1995;Ahmed et al, 1997;Byrne and Willis, 2005;Myburgh, 2005). It may be these teachers' misunderstanding of the nature and importance of a professional accounting career that could be contributing to the students' misperceptions of the accounting profession (Albrecht and Sack, 2000).…”
Section: Introductionmentioning
confidence: 99%